Jia-Wei-Si-Miao-Yong-An decoction modulates intestinal flora and metabolites in acute coronary syndrome model - Zhao, Ning; Wang, Ying; Ma, Yan; Liang, Xiaoxue; Zhang, Xi; Gao, Yuan; Dong, Yingying; Bai, Dong; Hu, Jingqing (Frontiers in Cardiovascular Medicine, 2023)
Aims We assessed the efficacy of the traditional Chinese medicine formulation Jia-Wei-Si-Miao-Yong-An decoction (HJ11) in the treatment of acute coronary syndrome and evaluated its impact on the intestinal microbiota and their metabolites. Methods An acute coronary syndrome model was established in rats, which were randomly assigned to the model, HJ11 treatment, and atorvastatin treatment groups. Rats were then administered saline solution (model and sham operation control groups) or drugs by oral gavage for 28 d. Echocardiography was performed and serum creatine kinase-MB and cardiac troponin I levels were monitored to examine the cardiac function. Inflammation was evaluated using hematoxylin and eosin staining of heart tissue, and serum interleukin-2, interleukin-6, tumor necrosis factor alpha, and high-sensitivity C-reactive protein measurements. Gut microbiota composition was analyzed via 16S rRNA gene sequencing. Metabolomics was used to determine fecal metabolites and elucidate the modes of action of HJ11 in acute coronary syndrome treatment. Results HJ11 improved cardiac function and attenuated inflammation in rats with acute coronary syndrome. Relative to the untreated model group, the HJ11-treated group presented normalized Firmicutes/Bacteroidetes ratio and reduced abundances of the bacterial genera norank_f__Ruminococcaceae, Desulfovibrio, Clostridium_sensu_stricto_1, Adlercreutzia, Staphylococcus, Bacteroides, Prevotella, Rikenellaceae_RC9_gut_group, unclassified_o__Bacteroidales, and Ruminococcus_gauvreauii_group. We found 23 differentially expressed intestinal metabolites, and the enriched metabolic pathways were mainly related to amino acid metabolism. We also discovered that asymmetric dimethylarginine levels were strongly associated with cardiovascular disease. Correlation analyses revealed strong associations among intestinal microflora, their metabolites, proinflammatory factors, and cardiac function. Hence, the therapeutic effects of HJ11 on acute coronary syndrome are related to specific alterations in gut microbiota and their metabolites. Conclusion This work demonstrated that HJ11 effectively treats acute coronary syndrome. HJ11 seems to increase the abundance of beneficial bacterial taxa (Bacteroides and Rikenellaceae_RC9_gut_group), mitigate the risk factors associated with cardiovascular disease, alter bacterial metabolites, lower asymmetric dimethylarginine levels, and effectively treat acute coronary syndrome.